A model analysis on the knowledge, attitude, and readiness of ELVs policy among Malaysians: A cross-sectional study - Ismail, Rozmi; Sitinjak, Charli; Tahir, Zurinah; Che Rose, Rosniza Aznie; Mat Yazid, Muhamad Razuhanafi; Harun, Zambri; Suparjo Noordin, Nur Atiqah (Frontiers in Built Environment, 2023)
The issue of end-of-life vehicles (ELV) in Malaysia has recently received serious attention from the government. The Malaysian government has launched various programs to reduce the number of ELVs that have not been adequately managed. Initiatives like offering rewards to those who want to turn up their damaged vehicles are similar to An effort to trade in their old automobiles. However, it was unsuccessful due to a lack of cooperation from Malaysians. This study examines the sociological aspects of community acceptance of ELV legislation in Malaysia. This study assesses community knowledge, attitudes, and readiness to implement ELV management in Malaysia. Six hundred thirty people participated in a cross-sectional survey performed across Malaysian states (Pulau Pinang, Kelantan, Johor, Melaka, Selangor, and Kuala Lumpur). A collection of questions was distributed face-to-face after satisfying the steps of validity and reliability tests. Then descriptive and multiple regression tests were run to determine correlations between variables. We use the structural equation model to determine the model in this research. The study’s findings revealed that people’s knowledge, attitudes, and readiness toward ELV policies were significantly influenced by their length of stay, level of education, and vehicle ownership (overall R2 = 0.663, VIF = 1,612, p = 0.000). It was also discovered that knowledge and attitude together could determine community readiness in implementing ELV policies in Malaysia. The findings of this study demonstrate how important it is for the government to consider the populace’s knowledge and attitudes before implementing the ELV policy in Malaysia.